Increasing Independence and Self-Management Ability of Santri Through “Kepemimpinan Bertumbuh” Motivation Training - Ahmad Nurkhin; S Martono; Muhsin Muhsin; Anna Kania Widiatami; Satsya Yoga Baswara; Hasan Mukhibad (Universitas Negeri Semarang, 2023)
Islamic boarding schools and Santri are two important elements that can impact improving the quality of human resources in Indonesia. The problems community service partners face include Santri' independence and self-management abilities. To overcome this problem, the FE UNNES community service team offered Kepemimpinan Bertumbuh motivational training. Leadership is an important aspect that Santri must possess. The method of implementing the chosen community service activities is motivational training, an activity that can inspire and entertain. The community service team present the material enthusiastically, inspires and touches the Santri' hearts. The community service team has been trained in many training and motivational activities, so they have adequate abilities. The dedication team try to give the best by combining various presentation media. Community service activities have been held in two stages of implementation. The first was held on April 1 2022, with the target of activities namely the administrators of the As Salafy Al Asror Patemon Islamic boarding school, Semarang City. Second, it was held on July 7 2022, with Santri as activity participants. Both activities can run well, as seen by the presence and participation of activities. The first form of activity is Kepemimpinan Bertumbuh training, while the second form of activity is motivational training. The resource person for the activity was Ahmad Nurkhin, S.Pd., M.Sc., assisted by other community service teams. The caretaker of the boarding school, KH Al Mamnuhin Kholid, supports this activity and reinforces the importance of self-management, both by administrators and Santri. Pesantren dan santri merupakan dua elemen penting yang dapat berdampak pada peningkatan kualitas SDM di Indonesia. Permasalahan yang dihadapi mitra pengabdian diantaranya mengenai kemandirian dan kemampuan manajemen diri santri. Untuk mengatasi masalah ini, tim pengabdian FE UNNES menyodorkan training motivasi kepemimpinan bertumbuh. Kepemimpinan merupakan aspek penting yang harus dimiliki oleh santri. Metode pelaksanaan kegiatan pengabdian yang dipilih adalah training motivasi, sebuah kegiatan yang dapat menggugah dan menghibur. Tim pengabdian akan berusaha menyajikan materi dengan penuh semangat, menggugah, dan menyentuh hati santri. Tim pengabdian telah terlatih dalam banyak kegiatan training dan training motivasi, sehingga memiliki kemampuan yang memadai. Dengan menggabungkan berbagai media presentasi, tim pengabdian akan berusaha untuk memberikan yang terbaik. Kegiatan pengabdian kepada masyarakat telah diselenggarakan dalam dua tahapan pelaksanaan. Pertama, dilaksanakan pada tanggal 1 April 2022 dengan sasaran kegiatan yaitu pengurus pondok pesantren As Salafy Al Asror Patemon Kota Semarang. Kedua, dilaksanakan pada tanggal 7 Juli 2022 dengan santri sebagai peserta kegiatan. Kedua kegiatan dapat berjalan dengan baik dilihat dengan kehadiran dan partisipasi kegiatan. Bentuk kegiatan pertama adalah pelatihan kepemimpinan bertumbuh sedangkan bentuk kegiatan kedua adalah training motivasi. Narasumber kegiatan adalah Ahmad Nurkhin, S.Pd., M.Si. dibantu tim pengabdian lainnya. Pengasuh pondok, KH Al Mamnuhin Kholid sangat mendukung kegiatan ini dan memberikan penguatan pentingnya manajemen diri, baik oleh pengurus dan santri.